Evaluation of Bioelectrical Activity of Pelvic Floor Muscles and Synergistic Muscles Depending on Orientation of Pelvis in Menopausal Women with Symptoms of Stress Urinary Incontinence: A Preliminary Observational Study. (19th February 2014) - Halski, Tomasz; Słupska, Lucyna; Dymarek, Robert; Bartnicki, Janusz; Halska, Urszula; Król, Agata; Paprocka-Borowicz, Małgorzata; Dembowski, Janusz; Zdrojowy, Romuald; Ptaszkowski, Kuba
Abstract : Objectives . Evaluation of resting and functional bioelectrical activity of the pelvic floor muscles (PFM) and the synergistic muscles, depending on the orientation of the pelvis, in anterior (P1) and posterior (P2) pelvic tilt. Design . Preliminary, prospective observational study. Setting . Department and Clinic of Urology, University Hospital in Wroclaw, Poland. Participants . Thirty-two menopausal and postmenopausal women with stress urinary incontinence were recruited. Based on inclusion and exclusion criteria, sixteen women aged 55 to 70 years were enrolled in the study. Primary Outcome Measures . Evaluation of resting and functional bioelectrical activity of the pelvic floor muscles by electromyography (sEMG) and vaginal probe. Secondary Outcome Measures . Evaluation of activity of the synergistic muscles by sEMG and surface electrodes. Results . No significant differences between orientations P1 and P2 were found in functional and resting sEMG activity of the PFM. During resting and functional PFM activity, higher electrical activity in P2 than in P1 has been recorded in some of the synergistic muscles. Conclusions . This preliminary study does not provide initial evidence that pelvic tilt influences PFM activation. Although different activity of synergistic muscles occurs in various orientations of the pelvic tilt, it does not have to affect the sEMG activity of the PFM.